Ovarian torsion during ovarian stimulation prior to trigger followed by successful oocyte retrieval: A case report - Mackenzie N. Naert; Sarah Baker; Jill Attaman; Mary E. Morris; Irene Souter; Victoria W. Fitz (Elsevier, 2023)
Objective: To report a case of ovarian torsion during ovarian stimulation prior to trigger followed by laparoscopic detorsion, trigger, and subsequent successful oocyte retrieval, as well as to review outcomes from the cycle. Case Presentation: A 32-year-old woman with a history of recurrent ovarian torsion presented with ovarian torsion during ovarian stimulation for in vitro fertilization prior to trigger injection. She underwent laparoscopic ovarian detorsion followed by trigger and oocyte retrieval.The rate of fertilization and blastocyst conversion of oocytes retrieved from the ovary affected by torsion was lower than from the contralateral ovary. Viable oocytes and an embryo were produced by the affected ovary. Conclusion: Ovarian torsion during ovarian hyperstimulation for in vitro fertilization is a rare occurrence, particularly prior to trigger. Clinicians can consider proceeding with trigger and oocyte retrieval after treating ovarian torsion in appropriately counseled patients.